Proceedings of International Seminar on Livestock Production and Veterinary Technology 2017
DOI: 10.14334/proc.intsem.lpvt-2016-p.37-44
|View full text |Cite
|
Sign up to set email alerts
|

Genotyping of Kappa-Casein Gene of Buffalo in Indonesian

Abstract: Casein (KCN) is a milk protein with four variants of alpha S1, alpha S2, beta and kappa which has different allel of each. Kappa Casein (CSN3) gene lies at exon 4 associating with fat and protein milk contens. Genetic variation of CSN3 gene influences quality and composition of milk. The aim of this research was to genotype the CSN3 gene of Bufalos from several places in Indonesia. Amount of 29 buffalo samples was used in this research, those consisted of 15 collected from Medan, 3 samples of Banyuwangi, 10 sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 11 publications
1
3
0
Order By: Relevance
“…PCR-RFLP results using AcuI enzyme disagreed with the majority of reviewed PCR-RFLP studies conducted by HindIII , HinfI or MaeII restriction enzymes which concluded that, all Egyptian buffaloes were monomorphic and genotyped as homozygous "BB" animals as reported by Othman (2005); El-Rafey and Darwish (2008); and Abdel Dayem et al (2009). Similar results were also noticed, in Pakistani buffalo (Riaz et al, 2008;Ghafoor et al, 2015), in Indian buffalo (Gangaraj et al, 2008;Shende et al, 2009;Nair et al, 2011;George et al, 2018), in Brazilian buffalo (Otaviano et al, 2005), in Chinese water buffalo (Ren et al, 2011) , in Iraqi buffalo (Jaayid et al, 2013), in Anatolian water buffalo breed (Cinar et al, 2016), in swamp and river Indonesian buffaloes (Margawati et al, 2016), in Cuban buffalo (Marrero et al, 2016), and in Iranian buffalo (Abbasi et al, 2009).…”
Section: Detection Of Polymorphism and Genetic Variants Of κ-Cn And β-Lgsupporting
confidence: 53%
“…PCR-RFLP results using AcuI enzyme disagreed with the majority of reviewed PCR-RFLP studies conducted by HindIII , HinfI or MaeII restriction enzymes which concluded that, all Egyptian buffaloes were monomorphic and genotyped as homozygous "BB" animals as reported by Othman (2005); El-Rafey and Darwish (2008); and Abdel Dayem et al (2009). Similar results were also noticed, in Pakistani buffalo (Riaz et al, 2008;Ghafoor et al, 2015), in Indian buffalo (Gangaraj et al, 2008;Shende et al, 2009;Nair et al, 2011;George et al, 2018), in Brazilian buffalo (Otaviano et al, 2005), in Chinese water buffalo (Ren et al, 2011) , in Iraqi buffalo (Jaayid et al, 2013), in Anatolian water buffalo breed (Cinar et al, 2016), in swamp and river Indonesian buffaloes (Margawati et al, 2016), in Cuban buffalo (Marrero et al, 2016), and in Iranian buffalo (Abbasi et al, 2009).…”
Section: Detection Of Polymorphism and Genetic Variants Of κ-Cn And β-Lgsupporting
confidence: 53%
“…Many researchers have reported that genotype in kappa casein gene associated with milk yield (Vidović et al, 2013;Deb et al, 2014), milk fat yield (Djedović et al, 2015), and cheese yield (Azevedo et al, 2008). In buffalo, kappa casein gene was observed for milk production traits (Patel et al, 2007b;Margawati et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The study of CSN3 gene reported by Margawati et al . [ 84 ] showed that all samples possessed BB genotypes, which merged the pattern of the digested fragments with sizes of 255 and 154 bp. This finding suggests that genotyping using HindIII reveals monomorphic BB types associated with milk content of casein.…”
Section: Development Of Genetic Studies In Indonesian Indigenous Buffalomentioning
confidence: 99%